Evaluación de la actividad fotocatalítica del tio2 soportado en carbón activado para la degradación de azul de metileno (2018)
In this research project, a composite was prepared using Titanium Dioxide and Activated Carbon that fulfilled the role of photocatalyst in the process of AM removal by heterogeneous photocatalysis. The direct impregnation method was used to achieve the fixation of TiO2 on the AC. The effect of the calcination temperature at 500 and 630 ° C and the relationship between the amount of TiO2 and AC in the preparation of the photocatalyst was analyzed. Adsorption and photodegradation tests were carried out for a total time of 4 and 3 hours in order to evaluate the photocatalytic activity of the samples obtained. The monitoring for each of the tests was carried out by the spectrophotometry method where the data were collected and plotted to observe the behavior of each of the prepared composites. The tests carried out allowed to quantify the performance of each composite in the removal of AM at a concentration of 7ppm in the presence of visible light. The samples calcined at 630 ° C showed better removal rates of the contaminant with 95.58 and 99.34%